Traffic jam : ten years of 'sustainable' transport in the UK / edited by Iain Docherty and Jon Shaw. - Docherty, Iain; Shaw, Jon (Professor of Transport Geography) (Policy Press, 2008)
This informed and lively book offers a timely analysis of the UK government's sustainable - or subsequently 'integrated' - transport policy 10 years after the publication of A New Deal for Transport: Better for Everyone. Written by prominent transport experts and with a foreword by Christian Wolmar, the book identifies the modest successes and, sadly, the far more significant failures in government policy over the last decade. The authors also uncover why it has proved so difficult to adopt a more sustainable approach to transport and break Britain's love-affair with the car. The book reviews the links between the idea of sustainability and transport policy, and provides an up-to-the-minute analysis of the political realities surrounding the delivery of a sustainable transport agenda in the UK. It picks up on the principal components of A New Deal for Transport and evaluates to what extent these have, or haven't, been delivered in England, Scotland, Wales and Northern Ireland. The contributors analyse why delivering sustainable transport policies seems to present particular difficulties to ministers across the UK, and considers the UK's experience in an international perspective. The book draws lessons from the last 10 years in order to better inform future policy development. Traffic Jam is an indispensable analysis of the difficulties involved in turning policy ideals into practical reality, and as such will be of interest to scholars, students, planners, policy analysts and policy makers.